If it's not what You are looking for type in the equation solver your own equation and let us solve it.
290=x+(x*2/3)
We move all terms to the left:
290-(x+(x*2/3))=0
We add all the numbers together, and all the variables
-(x+(+x*2/3))+290=0
We multiply all the terms by the denominator
-(x+(+x*2+290*3))=0
We calculate terms in parentheses: -(x+(+x*2+290*3)), so:We get rid of parentheses
x+(+x*2+290*3)
We add all the numbers together, and all the variables
x+(x*2+870)
We get rid of parentheses
x+x*2+870
Wy multiply elements
x+2x+870
We add all the numbers together, and all the variables
3x+870
Back to the equation:
-(3x+870)
-3x-870=0
We move all terms containing x to the left, all other terms to the right
-3x=870
x=870/-3
x=-290
| 290=x+(x/2/3) | | 5-2x^2=7 | | 5-2x^2=7 | | 3x2−17x+10=03x2−17x+10=0 | | 3x2−17x+10=03x2−17x+10=0 | | 5-2x^2=6 | | 90=2x+30 | | 90=2x+30 | | 5-2x^2=6 | | 5-2x^2=6 | | 5-2x^2=6 | | 15n^2-6n=0 | | 5-2x^2=6 | | (6+v)(4v-3)=0 | | 3y=6+(2+y) | | 2-x=8+5x | | 2-x=8+5x | | 3y=6+2+y) | | 15n^2-6n=0 | | 15n^2-6n=0 | | 15n^2-6n=0 | | (6+v)(4v-3)=0 | | 6^(x+1)=36 | | (6+v)(4v-3)=0 | | 2(1x+9)=20 | | 2(1x+9)=20 | | 3(1x+10)=30 | | 6.5g+8=1.5g+18 | | 6.5g+8=1.5g+18 | | 6.5g+8=1.5g+18 | | 6.5g+8=1.5g+18 | | 6.5g+8=1.5g+18 |